Teknologi Pendidikan: Kajian Aplikasi Ruangguru Berdasarkan Prinsip dan Paradigma Interaksi Manusia dan Komputer - Dian Rahadian; Gina Rahayu; Risma Rahma Oktavia (Institut Pendidikan Indonesia, 2019)
Abstract - This Ruangguru application study aims to determine the relevance of applicationfunctions based on the principles and paradigms of Human and Computer Interaction (HCI). In thisstudy, the aspects evaluated included aspects of human, technology, usability, and ergonomics. Theinterest in studying the Ruangguru application is based on several sources stating that Ruangguruis believed to be